Bone Phenotyping Approaches in Human, Mice and Zebrafish – Expert Overview of the EU Cost Action GEMSTONE (“GEnomics of MusculoSkeletal traits TranslatiOnal NEtwork”) - Foessl, Ines; Bassett, J. H. Duncan; Bjørnerem, Åshild; Busse, Björn; Calado, Ângelo; Chavassieux, Pascale; Christou, Maria; Douni, Eleni; Fiedler, Imke A. K.; Fonseca, João Eurico; Hassler, Eva; Högler, Wolfgang; et al. (Frontiers in Endocrinology, 2021)
A synoptic overview of scientific methods applied in bone and associated research fields across species has yet to be published. Experts from the EU Cost Action GEMSTONE (“GEnomics of MusculoSkeletal Traits translational Network”) Working Group 2 present an overview of the routine techniques as well as clinical and research approaches employed to characterize bone phenotypes in humans and selected animal models (mice and zebrafish) of health and disease. The goal is consolidation of knowledge and a map for future research. This expert paper provides a comprehensive overview of state-of-the-art technologies to investigate bone properties in humans and animals – including their strengths and weaknesses. New research methodologies are outlined and future strategies are discussed to combine phenotypic with rapidly developing –omics data in order to advance musculoskeletal research and move towards “personalised medicine”.